Leisure, interpersonal relationships, learning and consumption: the four key dimensions for the study of minors and screens (Communication & Society, 2012)
This study focuses on the needs Spanish minors wish to satisfy in their use of three types of screens (computers/the Internet, cell phones and video games) which can be included in the dimensions of relationships, leisure, learning and consumption. Using a representative sample of the school population in Spain aged between 10 and 18, collected in 2009, principal component analysis is applied to better understand the use of screens and see how these dimensions often interact. This analysis takes into account the gender and age variables of the respondents.